Samer genom tre prästers övervakande ögon : En postkolonial studie av tre prästers porträttering av samer och deras kultur från 1740- till 1830-tal. - Bredgaard, Linus (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2021)
This essay studies and compares three clergymen that were stationed in Sápmi during the eighteenth and nineteenth centuries and their writings that deal with the Saami population of the northern parts of Sweden. How they portray the Saami people and their culture is analyzed though postcolonial concepts as Edward Said’s othering and other concepts by the likes of Loomba, Lincoln and Pratt. The three priests portrayal of the Saami people and their culture are similar In that way that they all confirm some of the colonial stereotypes of the Saami during the time they were writing. But especially one of the priests stands out in his effort to give a nuanced portrayal of the Saami people.